Compositional and Sr‐Nd isotopic features of the Xiejiayao ophiolite in the North Qilian Orogenic Belt, NW China: Implications for the petrogenesis and tectonic setting. Issue 5 (12th January 2022) - Zhao, Cong; Zhao, Jing; Ni, Shijun; Chen, Youliang; Huang, Luyu
Abstract : The ophiolites along the North Qilian Orogenic Belt are considered to be fragments of ancient oceanic crusts and lithospheric mantle of the Palaeozoic North Qilian Ocean (a branch of the Proto‐Tethys). Compared with other ophiolites in this belt, the genesis of the Xiejiayao ophiolite has been poorly studied so far, making it difficult to understand the tectonic evolution of the ocean. In this study, we present new compositional and Sr‐Nd isotopic analyses of basaltic rocks from the Xiejiayao ophiolite to shed light on its petrogenesis and geodynamic background. These oceanic basalts are characterized by flat REE patterns, low elemental ratios of high‐field‐strength elements (e.g., La/Sm, Sm/Yb, La/Yb, Gd/Yb, [Th/Yb]PM ) and abundant spinels, implying that they were generated via partial melting in the spinel stability field of the mantle. Their positive εNd (t) values (6.1–8.4), high Zr/Nb (43.65–79.40) as well as low Nb/Ta (10.91–15.09), Zr/Hf (34.64–39.28), and Nb/Yb (0.41–0.59) ratios further reflect that the ancient mantle had already become depleted to some extent before the onset of the Palaeozoic ocean. Additionally, basalts share many geochemical similarities (e.g., Zr, Y, Ti, and V) with both mid‐ocean ridge and island arc basalts. This supports the strong likelihood of origin in a back‐arc basin close to the suprasubduction zone for the ophiolite. Therefore, accompanied by the northward subduction of the oceanic lithosphere during the early Palaeozoic, a large‐scale back‐arc basin developed progressively in response to the back‐arc expansion. The Xiejiayao basaltic magmas were generated in the back‐arc basin via partial melting of the depleted mantle and their source was probably mixed with subducted melts/fluids from the dehydration and melting of oceanic slabs and sediments. Abstract : The basaltic oceanic crust was derived from the previously depleted mantle and their magmatic source was mixed with slab melts/fluids. The tectonic setting of the ophiolite belonged to a back‐arc basin.